Behçet Necatigil ve Hermann Hesse'nin şiirlerinde ruh-beden çatışması - Tezgör, Hilmi. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2004., 2004)
Behçet Necatigil and Hermann Hesse are two great poets with many common points, even though they seem quite different at first sight. Behçet Necatigil, whose works reflect his life, has the same concept also for the translated poems. Necatigil, rather preferred working on poets, who have similar points of view with him, who he could build spiritual and sensitive connections with, and of course on those he liked. Hesse was one of those.This thesis approaches the tension that a person goes through when working on his/her self-realization and happiness, that is present in Necatigil's and Hesse's work within the frame of the Austrian philologist Leo Spitzer. In this thesis, concentration is on 'soul-body duality' in Neactigil's and Hesse's works, whether there is a final consensus, the differences or similarities concerning the theme used, how the poets use the spaces and its reflections on one, again differeneces and similarities of how the tension is expressed in words and finally on techniques used to transfer these issues into literature. In Necatigil's works, soul "went away" but the body "stayed"; in Hesse's works both soul and body "went away."
Keywords: Turkish literature.